Impact of body mass index and low estrogen level on urinary hydroxyl proline and other bone related parameters in postmenopausal women - Paneri, Sangita; Panchonia, Ashok; Varma, Meena; Sarkar, Purnima Dey; Yadav, Sumitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The study revealed the impact of body mass index and low estrogen level on urinary hydroxyl proline and other bone related parameters in postmenopausal women. Methods: The study comprised 145 obese postmenopausal women and 145 ideal weight postmenopausal women as a study subjects and 145 normal reproductive age group women taken as control. The following biochemical parameters serum calcium, serum phosphorous, serum alkaline phosphatase, urinary calcium, urinary creatinine, urinary hydroxyproline were estimated for assessment of bone loss. Then these results were compared with control group. Results: The significant changes found in biochemical parameters in ideal weight postmenopausal women and highly significant changes in biochemical parameters observed in obese post menopause women. Conclusions: The obese postmenopausal women who have high BMI and low estrogen level have higher bone loss and are more prone to suffer from bone related problems.